Internal communications : a manual for practitioners - FitzPatrick, Liam.; Valskov, Klavs (2014)
"Bad company communication can result in high staff turnover, poor results and low morale. Internal Communications draws on examples of best practice in the private, public and non-profit sectors, with case studies of high profile international organizations. The book defines and explains internal communications (IC), providing practical, ready to implement guidance on planning and organizing the IC function and IC teams; understanding audiences; deciding and developing messages; channels, outcomes and approaches; line managers and leadership; evaluating and reporting; advising leaders; and change and transitions. The advice in the book is accompanied by downloadable templates for communications in a variety of special situations -- from crises to mergers to business strategies and rebranding. Covering all the core concepts and models, skills and processes, Internal Communications offers a refreshingly practical introduction for students and practitioners alike. "--
"Get internal communications right in your organization and the benefits are clear. Motivated staff, better financial performance, a strong external reputation and delighted customers are just a few of the reasons why getting your message over to staff effectively matters. Internal Communications explores what good practice in internal communications looks like, providing a no-nonsense approach to devising an internal communications strategy based on the authors' extensive experiences as consultants and in-house leaders in the private, public and not-for-profit sectors. It provides a step-by-step guide to
Machine generated contents note: List of figures -- List of tables -- Foreword by Anne Gregory -- Foreword by James Harkness -- AcknowledgementsBefore we start01 What internal communication is and why it matters -- What you will learn from this chapter -- Internal communication is coming of age -- Definitions -- It's not about telling - it's a two-way thing -- Getting strategic -- Ethics -- The key learning points from this chapter -- Notes and references02 Organizing internal communication -- What you will learn from this chapter -- A little history -- The big answer -- How do you decide what you need? -- Working with suppliers -- The key learning points from this chapter -- Notes and references03 Planning -- What you will learn from this chapter -- The essential steps of planning -- Templates for a communication plan -- The key learning points from this chapter04 Audiences -- What you will learn from this chapter -- Why understanding your audience is important -- The basics - the demographics every internal communicator needs to know -- Segmentation: One size does not fit all! -- The key learning points from this chapter -- Notes and references05 Messaging -- What you will learn from this chapter -- What is a message? -- Making it supportable -- Making the case for a change - dilemmas, proof and emotion -- Keeping it simple -- Planning your message - a standard template -- Channels and messages -- The key learning points from this chapter -- Notes and references06 Channels -- What you will learn from this chapter -- It's all about results -- The medium is the message -- Social media - misunderstandings and opportunities -- Conducting a basic channels audit -- Discovering what good looks like -- A channels matrix -- The key learning points from this chapter -- Notes and references07 Why line managers matter and how to support them -- What you will learn from this chapter -- The line manager as the make-or-break factor -- It's not what you do but the way that you do it: the five key questions -- The key learning points from this chapter -- Notes and references08 Working with senior leaders -- What you will learn from this chapter -- Why should anyone care about making the CEO look good? -- The boss and engagement -- Why should the IC team care? -- What does it mean to be a 'trusted adviser'? -- Getting your plan sorted -- Channels and tools that work -- The key learning points from this chapter -- Notes and references09 Change -- What you will learn from this chapter -- What is change? Getting the terms right -- Some theory -- A planning template -- Preparing leaders -- Keeping communications going through the life of a change -- The key learning points from this chapter -- Notes and references10 Research and evaluation for internal communicators -- What you will learn from this chapter -- Why do internal communicators need data? -- What should you measure? -- Audits - creating the communicators' balance sheet -- Where can you find your data? -- Quantitative measures - surveys and tracking -- Qualitative approaches -- Resources -- The key learning points from this chapter -- Notes and references11 Developing yourself and the team -- What you will learn from this chapter -- What makes a great IC professional? -- It's about the role -- What skills, knowledge or experience do I need to do a good job? -- How do I get better? -- The key learning points from this chapter -- Notes and referencesAppendix 1: The CIPR Code of Conduct -- Appendix 2: Dewhurst and FitzPatrick's core competencies -- Index.
Keywords: Business communication; Communication in management; Communication in organizations; BUSINESS & ECONOMICS / Business Communication / General; BUSINESS & ECONOMICS / Management; BUSINESS & ECONOMICS / Organizational Development; BUSINESS & ECONOMICS / Public Relations; Print books